A comparative study of analgesic property of whole plant and fruit extracts of Fragaria vesca in experimental animal models - Lalit Kanodia; Swarnamoni Das (Bangladesh Pharmacological Society, 2009)
The aim of the study was to compare the analgesic activities of ethanolic extract of fruits and whole plant of Fragaria vesca in experimental animal models. The extracts were prepared by percolation method and oral toxicity testing was performed as per OECD guidelines. Analgesic activity was assessed by tail flickmethod (for central action) and acetic acid-induced writhing test (for peripheral action). Fruit extract, whole plant extract and aspirin showed significant analgesic activity, both central and peripheral, as compared to control (p< 0.01). Although fruit extract at dose of 500 mg/kg showed better activity than 250 mg/kg (p<0.05). Analgesic activities of fruit extract 250 mg/kg and whole plantextract 500 mg/kg were almost equivalent while aspirin was most potent among all with significantly greater activities as compared to all the extracts (p<0.05).